An Overview: Coronaviruses in Recent Two Decades - H. Al-Mashhadani, Mohammed; Mohammed, Alaa; Raheem, Rasha; Yousif, Emad (Al-Nahrain Journal of Science, 2021)
Coronaviruses are an association of viruses which lead sicknesses in mammals and birds. The Common symptoms that affect humans are respiratory tract infections, fever, headache, etc. In this review, we highlight the development in coronaviruses in recent two decade, which include simple acute respiratory syndrome (2002-2003), middle east respiratory syndrome (2012) and coronavirus disease 2019 (2019-2020).